Desain Perangkat Pembelajaran Pendidikan Tinggi dengan Sistem Lective Gegulang™ - Galih Wasis Wicaksono; Hari Windu Asrini; Muhammad Andi Al-Rizki (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Syllabus and lesson plan (RPS and RPP in Indonesian), which consist of topics and plan for conducting a subject during a period of time, are essential elements for teaching and learning activity. Therefore, in order to conduct subject successfully, syllabus and learning plan should be revised before class started. However, the revising activity is not a simple activity and sometimes becomes a complex activity that takes time. Consequently, in many cases, teachers tend to regret doing this activity; and if do so the maximal result will not be achieved. To solve this problem, Lective Gegulang™ was built to help teacher managing syllabus and lesson plan. Using Lective Gegulang, a teacher is able to work collaboratively by sharing their documents and discussing their work. Lective Gegulang is an interactive tool that adapts dynamically to high education policy and any possible changes, so, it is easy for the teacher to modify their syllabus and lesson plan; and then evaluates its consistency. Then, testing was conducted by four education experts by validating 13 features of Lective Gegulang. The result shows that 48.1% of all features are completely compliance with the syllabus and lesson plan development flow. Then, 46.1% of features are compliance with minor improvement and 5.8% of features need major improvement. Moreover, Lective Gegulang was successfully implemented in Informatics Department, Universitas Muhammadiyah Malang, with all features was fulfilling all requirements needed.